2017
DOI: 10.1063/1.4978270
|View full text |Cite
|
Sign up to set email alerts
|

Strain-mediated 180° switching in CoFeB and Terfenol-D nanodots with perpendicular magnetic anisotropy

Abstract: A micromagnetic and elastodynamic finite element model is used to compare the 180° out-of-plane magnetic switching behavior of CoFeB and Terfenol-D nanodots with perpendicular magnetic easy axes. The systems simulated here consist of 50 nm diameter nanodots on top of a 100 nm-thick PZT (Pby[ZrxTi1-x]O3) thin film, which is attached to a Si substrate. This allows voltage pulses to induce strain-mediated magnetic switching in a magnetic field free environment. Coherent and incoherent switching behaviors are obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…Due to a limited number of single-phase multiferroic compounds operating at room temperature, composite multiferroics containing ferroelectric (or piezoelectric) and ferromagnetic components have been considered as viable candidates [8][9][10][11]. It was shown that composite multiferroic materials often have much larger magnetoelectric coupling compared to their single-phase counterparts, resulting from strain-mediated [12][13][14][15] or charge-mediated [16][17][18][19][20][21] coupling mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a limited number of single-phase multiferroic compounds operating at room temperature, composite multiferroics containing ferroelectric (or piezoelectric) and ferromagnetic components have been considered as viable candidates [8][9][10][11]. It was shown that composite multiferroic materials often have much larger magnetoelectric coupling compared to their single-phase counterparts, resulting from strain-mediated [12][13][14][15] or charge-mediated [16][17][18][19][20][21] coupling mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Computationally, there are several schemes [16][17][18][19][20][21][22][23] for achieving voltage-driven in-plane magnetization reversal under zero external magnetic fields mediated by strain 16,18,20,22,23 or exchange coupling. 17,21 By contrast, there is only one approach [24][25][26][27] for achieving voltage-driven perpendicular magnetization reversal under zero external magnetic fields, that is, using pulse-voltage-induced transient strains (through converse piezoelectric effect) to temporarily switch the perpendicular magnetic EA to the in-plane direction. Generally, a strain-mediated voltage-driven magnetization switching (in-plane or perpendicular, 90°or 180°) involves the following four coupled dynamic processes as outlined in Hu et al 2 : (i) establishment of the electric field in the piezoelectric, (ii) creation/release of strains, (iii) transfer of strain across the magnetic/piezoelectric interface, and (iv) strain-enabled magnetization switching in the magnet.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a strain-mediated voltage-driven magnetization switching (in-plane or perpendicular, 90°or 180°) involves the following four coupled dynamic processes as outlined in Hu et al 2 : (i) establishment of the electric field in the piezoelectric, (ii) creation/release of strains, (iii) transfer of strain across the magnetic/piezoelectric interface, and (iv) strain-enabled magnetization switching in the magnet. However, existing computational studies of strain-mediated voltage-driven magnetization reversal (that is, 180°switching) 16,[18][19][20][22][23][24][25][26][27] either did not consider the influence of the dynamics of process (ii) on process (iv) 16,[18][19][20][22][23][24][25][26] or did not consider the influence of the stiffness damping coefficient of the piezoelectric when modeling the dynamics of process (ii). 27 Furthermore, most of these studies 16,[18][19][20]22,[24][25][26][27] did not consider the influence of thermal fluctuations on process (iv).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the energy estimates provided in this manuscript neglect substrate clamping effects, which can be substantial with improperly designed systems. However, this issue has been considered by other researchers (e.g., Ref [38]), suggesting values below 275 aJ are feasible if the system is properly designed.…”
Section: Resultsmentioning
confidence: 98%